"We're playing on the same team": Communication (dis)connections between trauma patients and surgical residents. Issue 1 (12th January 2023) - Huang, Anna K.; Campbell, Paige-Ashley; Chaudhary, Mihir J.; Soklaridis, Sophie; Miller, Doriane; Dinizulu, Sonya; Stolbach, Bradley; Cosey Gay, Franklin; Washington, Stephanie; Olivera Perez, Henry; Chalmers, Kristen; Tessema, Frazer; et al.
Abstract : Trauma patients and surgery residents can feel disconnected due to differences in background and a lack of time for adequate communication, yet they understand each other's stressors and share a desire for increased communication and connection. Abstract : BACKGROUND: Patient-physician communication is key to better clinical outcomes and patient well-being. Communication between trauma patients and their physicians remains relatively unexplored. We aimed to identify and characterize the range of strengths and challenges in patient-physician communication in the setting of trauma care. METHODS: A qualitative, grounded theory approach was used to explore communication strengths and challenges for patients and residents. Patients previously admitted to the trauma service for violent injuries were recruited and interviewed in-person during their trauma clinic appointments. Surgical residents were recruited via email and interviewed virtually via Zoom. Anonymous, semistructured interviews were conducted until thematic saturation was reached. RESULTS: Twenty-nine interviews with patients and 14 interviews with residents were conducted. Patients reported feeling ignored and misunderstood and having inadequate communication with physicians. Residents cited lack of time, patients' lack of health literacy, differences in background, and emotional responses to trauma as barriers to effective communication with patients. Patients and residents reported an understanding of each other's stressors, similar emotional experiences regarding traumatic stress, and a desire to communicate with each other in greater depth both inside and outside of the hospital. CONCLUSION: Trauma patients and residents can feel disconnected due to the lack of time for thorough communication and differences in background; however, they understand each other's stressors and share similar emotional responses regarding trauma and a desire for increased communication, connection, and solidarity. Leveraging these shared values to guide interventions, such as a resident curriculum, may help bridge disconnects and improve their communication. LEVEL OF EVIDENCE: Therapeutic/Care Management; Level IV. Abstract :